Express Yourself: Why Managers' Disclosure Tone Varies Across Time and What Investors Learn from It - Campbell, John L.; Lee, Hye Seung “Grace”; Lu, Hsin‐Min; Steele, Logan B. (Contemporary Accounting Research, 2020)
ABSTRACT We argue that volatility in a manager's disclosure tone across time should be a function of two components: (i) the firm's innate operating risk and (ii) the extent to which the manager's disclosure transparently reflects that risk. Consistent with this argument, we find that both operating risk and disclosure transparency are important determinants of disclosure tone volatility. We then examine whether investors incorporate the incremental information provided by disclosure tone volatility into their assessments of firm risk. If disclosure tone volatility primarily provides investors with incremental information about a firm's operating risk, we should find a positive association between tone volatility and market‐based assessments of risk. On the other hand, if disclosure tone volatility primarily provides investors with incremental information about a manager's disclosure transparency, we should find a negative association between tone volatility and market‐based assessments of risk. Consistent with an operating risk explanation, we find a positive association between disclosure tone volatility and market‐based assessments of firm risk after controlling for a comprehensive set of proxies for operating risk and transparency. We find little support for an information risk explanation, even when we examine multiple measures specifically designed to capture information risk. Taken together, our results suggest that although disclosure tone volatility is a function of both a firm's operating risk and a manager's disclosure transparency, investors appear to respond as if disclosure tone volatility only provides incremental information about a firm's operating risk.